Comparing pre- and post-copulatory mate competition using social network analysis in wild crickets - Fisher, David N. (Behav Ecol, 2016)
Sexual selection results from variation in success at multiple stages in the mating process, including competition before and after mating. The relationship between these forms of competition, such as whether they trade-off or reinforce one another, influences the role of sexual selection in evolution. However, the relationship between these 2 forms of competition is rarely quantified in the wild. We used video cameras to observe competition among male field crickets and their matings in the wild. We characterized pre- and post-copulatory competition as 2 networks of competing individuals. Social network analysis then allowed us to determine 1) the effectiveness of precopulatory competition for avoiding postcopulatory competition, 2) the potential for divergent mating strategies, and 3) whether increased postcopulatory competition reduces the apparent reproductive benefits of male promiscuity. We found 1) limited effectiveness of precopulatory competition for avoiding postcopulatory competition; 2) males do not specifically engage in only 1 type of competition; and 3) promiscuous individuals tend to mate with each other, which will tend to reduce variance in reproductive success in the population and highlights the trade-off inherent in mate guarding. Our results provide novel insights into the works of sexual competition in the wild. Furthermore, our study demonstrates the utility of using network analyses to study competitive interactions, even in species lacking obvious social structure.